2023
DOI: 10.1038/s41467-023-39533-y
|View full text |Cite
|
Sign up to set email alerts
|

Nanoconfinement enabled non-covalently decorated MXene membranes for ion-sieving

Abstract: Covalent modification is commonly used to tune the channel size and functionality of 2D membranes. However, common synthesis strategies used to produce such modifications are known to disrupt the structure of the membranes. Herein, we report less intrusive yet equally effective non-covalent modifications on Ti3C2Tx MXene membranes by a solvent treatment, where the channels are robustly decorated by protic solvents via hydrogen bond network. The densely functionalized (-O, -F, -OH) Ti3C2Tx channel allows multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Ionic liquids (ILs) have high ionic conductivity, low vapor pressure, and excellent thermal stability, making them ideal candidates for energy storage, catalysis, and electrochemistry. However, one of the major challenges to restricting the wide use of ILs is their low ionic conductivity at low temperatures. Such low ionic conductivity of pure ILs is often due to their high viscosity and low diffusivity. ,, Our recent work found that the nanoconfinement effect of ILs within 2D materials can overcome these limitations by increasing the effective concentration of ions and reducing their mobility restrictions, thus enhancing ionic conductivity. , The nanoconfined effect is a phenomenon where the confinement of material in a nanostructure leads to changes in its properties due to the interaction between the material and the nanostructure. The confinement of ILs results in several interesting effects, including increased density, increased ionic conductivity, and enhanced ion-pairing and structural ordering. These effects are a direct result of the strong electrostatic interactions between the charged ions and the charged surfaces of the nanochannel.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs) have high ionic conductivity, low vapor pressure, and excellent thermal stability, making them ideal candidates for energy storage, catalysis, and electrochemistry. However, one of the major challenges to restricting the wide use of ILs is their low ionic conductivity at low temperatures. Such low ionic conductivity of pure ILs is often due to their high viscosity and low diffusivity. ,, Our recent work found that the nanoconfinement effect of ILs within 2D materials can overcome these limitations by increasing the effective concentration of ions and reducing their mobility restrictions, thus enhancing ionic conductivity. , The nanoconfined effect is a phenomenon where the confinement of material in a nanostructure leads to changes in its properties due to the interaction between the material and the nanostructure. The confinement of ILs results in several interesting effects, including increased density, increased ionic conductivity, and enhanced ion-pairing and structural ordering. These effects are a direct result of the strong electrostatic interactions between the charged ions and the charged surfaces of the nanochannel.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two-dimensional (2D) nanofluidic channels have emerged as promising candidates for efficient ion sieving as they combine the merits of a charged microenvironment and confined 2D nanochannels. More importantly, it is far more facile to fabricate and modify 2D channels. Generally, the sieving of the 2D nanofluidic channel is achieved by stacking the 2D nanosheets into lamellar membranes layer by layer via van der Waals forces. , MXene, a new type of 2D material known as transition-metal carbides or/and nitrides, has been extensively applied in lamellar membranes and shown outstanding sieving performance. , Ti 3 C 2 T x is one of the most studied MXene, , in which T represents the terminated groups, including –F, –OH, O. These functional groups allow the surface modification of MXene to tune the charge density or grafting ion-specific recognition molecules. For example, EtOH was chosen to decorate MXene by establishing multiple hydrogen bond membranes. After decoration, the membranes showed excellent proton-cation (H + /M n + ) selectivity up to 30 times higher than the pristine MXene membranes .…”
Section: Introductionmentioning
confidence: 99%
“…It remains a great challenge to construct such smart membranes with both a reversible ion-gating capability and desirable ion selectivity comparable to BICs. Recently, lamellar membranes stacked by two-dimensional (2D) Ti 3 C 2 T x nanosheets (a new 2D materials from the MXene family) have attracted extensive attention in ion separation due to the regularly aligned and highly designable 2D subnanochannels. However, the lack of rational design of binding sites leads to unsatisfactory ion selectivity and intelligence, and the mechanism of metal ion selective transport in 2D subnanochannels remains elusive. To this end, we propose a simple strategy to assemble p -phenylenediamine (PPD) molecules into the interlayer of the MXene membrane to deconstruct 2D subnanochannels with pH-sensitive and specific binding sites.…”
Section: Introductionmentioning
confidence: 99%